Ketamine as the anaesthetic for electroconvulsive therapy: The KANECT randomised controlled trial. (June 2017) - Fernie, Gordon; Currie, James; Perrin, Jennifer S.; Stewart, Caroline A.; Anderson, Virginica; Bennett, Daniel M.; Hay, Steven; Reid, Ian C.
Abstract : Background: Ketamine has recently become an agent of interest as an acute treatment for severe depression and as the anaesthetic for electroconvulsive therapy (ECT). Subanaesthetic doses result in an acute reduction in depression severity while evidence is equivocal for this antidepressant effect with anaesthetic or adjuvant doses. Recent systematic reviews call for high-quality evidence from further randomised controlled trials (RCTs). Aims: To establish if ketamine as the anaesthetic for ECT results in fewer ECT treatments, improvements in depression severity ratings and less memory impairment than the standard anaesthetic. Method: Double-blind, parallel-design, RCT of intravenous ketamine (up to 2 mg/kg) with an active comparator, intravenous propofol (up to 2.5 mg/kg), as the anaesthetic for ECT in patients receiving ECT for major depression on an informal basis. (Trial registration: European Clinical Trials Database (EudraCT): 2011-000396-14 and clinicalTrials.gov: NCT01306760.) Results: No significant differences were found on any outcome measure during, at the end of or 1 month following the ECT course. Conclusions: Ketamine as an anaesthetic does not enhance the efficacy of ECT.